2014
DOI: 10.3171/2013.12.jns13990
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery of brainstem cavernous malformations: a systematic review and meta-analysis

Abstract: Object Over the last two decades, stereotactic radiosurgery (SRS) has arisen as a promising approach in the management of brainstem cavernous malformations (CMs). In the present study, the authors report a systematic review and meta-analysis of the available published data regarding the radiosurgical management of brainstem CMs. Methods To identify eligible studies, systematic searches for brainstem CMs treated with SRS were conducted in major scientific publication databases. The search yielded 5 studies, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Given the inability to illustrate angiographic or radiographic obliteration of a CM after treatment, studies have instead relied on demonstrating a decrease in CM hemorrhage rate after SRS [59][60][61][62]. Lunsford and colleagues reported their results for SRS used in 103 patients with solitary, symptomatic CMs managed over a 17-year period [59].…”
Section: Radiosurgerymentioning
confidence: 98%
“…Given the inability to illustrate angiographic or radiographic obliteration of a CM after treatment, studies have instead relied on demonstrating a decrease in CM hemorrhage rate after SRS [59][60][61][62]. Lunsford and colleagues reported their results for SRS used in 103 patients with solitary, symptomatic CMs managed over a 17-year period [59].…”
Section: Radiosurgerymentioning
confidence: 98%
“…High-dose corticotherapy remains the main treatment of radiation injury in this location. The maximal efficiency of GKS appeared 2 years after radiosurgery according to some studies [14]. In our series, the AHR was similar before and after 2 years, maybe because of the limited number of patients.…”
Section: Discussionmentioning
confidence: 60%
“…The neurological status of the patient could deteriorate after the first hemorrhagic episode. The AHR in patients initially presenting with previous hemorrhage was estimated to be between 15 and 35% according to various studies [11,14]. Li et al [9] reported an AHR of 8.7% in patients presenting initially without hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations